2019
DOI: 10.1038/s41467-019-08500-x
|View full text |Cite
|
Sign up to set email alerts
|

Combining lifestyle risks to disentangle brain structure and functional connectivity differences in older adults

Abstract: Lifestyle contributes to inter-individual variability in brain aging, but previous studies focused on the effects of single lifestyle variables. Here, we studied the combined and individual contributions of four lifestyle variables - alcohol consumption, smoking, physical activity, and social integration - to brain structure and functional connectivity in a population-based cohort of 549 older adults. A combined lifestyle risk score was associated with decreased gyrification in left premotor and right prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 67 publications
3
43
1
2
Order By: Relevance
“…Furthermore, Lindbergh et al [43] found a stronger segregation of the DMN, expressed by a higher within-compared to between-network RSFC, over the course of aging to be associated with higher intelligence. Bittner et al [8] integrated different aspects of lifestyle into a lifestyle risk score including smoking and alcohol intake as risk factors and social interaction and physical activity as protective factors. Higher lifestyle risk was associated with higher between-network RSFC, i.e.…”
Section: Other Factors That Might Explain the High Inter-individual Vmentioning
confidence: 99%
“…Furthermore, Lindbergh et al [43] found a stronger segregation of the DMN, expressed by a higher within-compared to between-network RSFC, over the course of aging to be associated with higher intelligence. Bittner et al [8] integrated different aspects of lifestyle into a lifestyle risk score including smoking and alcohol intake as risk factors and social interaction and physical activity as protective factors. Higher lifestyle risk was associated with higher between-network RSFC, i.e.…”
Section: Other Factors That Might Explain the High Inter-individual Vmentioning
confidence: 99%
“…Acute alcohol intake by older individuals is associated with reduced cognitive function and blunted neural responses that mediate higher order working memory and attention as compared to younger adults (Lewis et al, 2019;Squeglia et al, 2014). Moreover, magnetic resonance imaging studies have shown that moderate, nondependent, alcohol use (Mukamal et al, 2001) or moderate alcohol use combined with reduced physical activity (Bittner et al, 2019) is associated with loss of gray matter in older adults, which may contribute to alcohol-induced cognitive decline. However, other evidence suggests that moderate alcohol use does not alter age-related cognitive decline (Moussa et al, 2014) suggesting that the conditions under which low to moderate levels of alcohol use may impact health and well-being in older populations are not fully understood.…”
Section: Alcohol Age-related Cognitive Decline and Dementiamentioning
confidence: 99%
“…Acute alcohol intake by older individuals is associated with reduced cognitive function and blunted neural responses that mediate higher order working memory and attention as compared to younger adults (Lewis, Garcia, Boissoneault, Price, & Nixon, 2019; Squeglia, Boissoneault, Van Skike, Nixon, & Matthews, 2014). Moreover, magnetic resonance imaging studies have shown that moderate, nondependent, alcohol use (Mukamal, Longstreth, Mittleman, Crum, & Siscovick, 2001) or moderate alcohol use combined with reduced physical activity (Bittner et al, 2019) is associated with loss of gray matter in older adults, which may contribute to alcohol-induced cognitive decline. However, other evidence suggests that moderate alcohol use does not alter age-related cognitive decline (Moussa et al, 2014) suggesting that the conditions under which low to moderate levels of alcohol use may impact health and well-being in older populations are not fully understood.…”
Section: Introductionmentioning
confidence: 99%